(NmODELX RELQTIWISTSKOJ STRUNY W FIZIKE ADRONOW (B/s - (NbARBA[OW(B, (NbORIS mIHAJLOWI^s; (NnESTERENKO(B, (NwLADIMIR wITALXEWI^s ((NmOSKWA (B:s (N|NERGOATOMIZDAT(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 168-174 (134 (NNAZW(B.)s
Keywords: (NaDRONY (B- (NfIZIKAs; (NkWANTOWAQ TEORIQ POLEJs